Pengaruh Harga dan Promosi terhadap Kepuasan Pelanggan Gojek - M. Alfitra Salam; Ilham Hidayah Napitupulu; Erwinsyah Simanungkalit; Harris Pinagaran Nst; Aulia Benazira (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This study aims to analyze the influence of price and promotion on Gojek customer satisfaction among students of the Business Administration Department at the State Polytechnic of Medan. This research uses a quantitative method with data collection through questionnaires, involving 101 respondents who are students of the Business Administration Department at the State Polytechnic of Medan and users of Gojek services. The data analysis technique used in this research is multiple linear regression analysis. The results show that price and promotion have a positive and significant impact on customer satisfaction. This means that the better the price and promotion offered by Gojek, the higher the level of customer satisfaction. These findings imply that Gojek management needs to continually pay attention to pricing and promotional strategies to improve customer satisfaction, especially among students.